Gadd45α: a novel diabetes-associated gene potentially linking diabetic cardiomyopathy and baroreflex dysfunction. - Ning Wang (Public Library of Science (PLoS), 2012)
Both diabetic cardiomyopathy (DCM) and baroreflex dysfunction independently contribute to sudden cardiac death (SCD), however the inherent connections between them under diabetic state remains unclear. As microRNAs (miRNAs) have been reported to participate in various physiological and pathological processes, we presume they may also be involved in DCM and DM-induced impairment of baroreflex sensitivity. Two sets of gene expression profiles data from streptozotocin (STZ)-induced diabetic heart and diabetic dorsal root ganglia (DDRG) were retrieved from GEO and ArrayExpress. Co-differentially-expressed genes in diabetic heart and DDRG were identified by t test and intersection analysis. Human Protein Reference Database (HPRD) was applied to find direct interacting proteins of Gadd45α. Differentially-expressed miRNAs in left ventricle from 4-week STZ-induced diabetic rats were screened by miRNA microarray. Expression of miR-499 and its regulating effect on Gadd45α were then verified by quantitative real-time PCR (qRT-PCR), western blot, computational predication, and dual-luciferase reporter analysis. Four co-differentially-expressed genes in DCM and DDRG were identified. Among these genes, Gadd45α has 16 direct interacting proteins and 11 of them are documentedly associated with DM. Accompanied with significantly increased miR-499 expression, Gadd45α expression was increased at mRNA level but decreased at protein level in both diabetic heart and nucleus ambiguous. Furthermore, miR-499 was confirmed negatively regulating Gadd45α by targeting its 3'UTR. Collectively, reduced Gadd45α protein expression by forced miR-499 expression indicated it's a diabetes-associated gene which might potentially be involved in both DCM and DM-induced baroreflex dysfunction.